Associations Between Health Behavior Habits and Quality of Life Outcomes in Pregnant Women: A Preliminary Investigation in Polish Sample - Justyna Krzepota; Dorota Sadowska (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2015)
The aim of our study was to analyze the relationships between health behaviours and quality of life. Research was conducted on a sample of 144 women in the third trimester of pregnancy, participating in antenatal classes. The tools used for investigation of health behaviour was Health Behaviour Inventory and for the quality of life was Quality of Life Questionnaire (WHOQoL-Bref). The analysis of results between women with high, average and low General Index of Intensity of Health Behaviours (GIIHB) showed statistically relevant difference in quality of life only in the Environment domain ( p ≤ 0.05). Depending on GIIHB, there are different correlations between categories of health behaviours and quality of life. The present research confirmed the existence of correlations between health behaviours and perceived quality of life among pregnant women participating in antenatal classes. The observed correlations show a need for further investigation and taking into account also other individual and socio-economic factors.